Assessing Multiplier Effects of Public Expenditures on Economic Growth in Nepal: SVAR Model Analysis - Raghu Bir Bista; Kiran Prasad Sankhi (Yayasan Ahmar Cendekia Indonesia, 2022)
This paper assesses the multiplier effects of public expenditures on economic growth in Nepal, covering time series data sets of public expenditures and economic growth from 1974-75 to 2018-19 by using the SVAR model. As a result of the SVAR model, the multiplier effect of public expenditure, recurrent expenditure, and capital expenditure is positive for economic growth. In a result, the multiplier effect of recurrent expenditure is found to be more promising than capital expenditure for economic growth in the short run, but in the long run, it is lower. Similarly, the multiplier coefficient value of capital expenditure is lower in the short run. This is probably due to leakages in the economy, corruption and improper management of development funds, seasonal expenditure trends, and poor management of development projects. Therefore, the government should improve the efficiency of public expenditure and the ratio of capital expenditure and private investment to improve the higher multiplier variable in the long run.